Caching in the Jordanian Author’s Right and Neighboring Rights Protection Law: A Comparative Study with the American and European Legislation - Haddadin , Suhail (Dirasat: Shari'a and Law Sciences, 2020)
This study is based on the argument that there is a real problem in the Jordanian law for the protection of copyright and related rights, which is the direct liability of telecommunications companies and search engines due to caching. This study will show that these acts, according to the Jordanian Copyright Law, constitute an infringement. Therefore, there is a real need for the legislator to intervene in order to ensure a balance between their interests and the interests of the content providers, so that the ISPs and search engines can work within a certain area without being held liable for the infringement of copyright. Both the American and European legislators have presented solutions that could serve as models for the Jordanian lawmaker if there was an intention to amend the law. By analysing the texts of these legislations, we will conclude that this legislation does not include the acts of caching done by search engines. Therefore, this study argues that this gap can be overcome by the implementation of the rule of “estoppel”, which states that "whoever sought to overturn what was done on his part, his endeavour is returned" stipulated in the Jordanian Civil Law, so that it gives the search engines enough space to practice temporary storage works. This study also recommends the necessity of introducing a special exception for ISPs that enables them to carry out intermediate caching without establishing responsibility for them, in order to protect national companies operating in this field from legal liability.